Does team communication represent a one-size-fits-all approach?: A meta-analysis of team communication and performance - Marlow, Shannon L.; Lacerenza, Christina N.; Paoletti, Jensine; Burke, C. Shawn; Salas, Eduardo (Organizational behavior and human decision processes, 2018)
•A meta-analysis of team communication and performance is conducted.•Team communication is significantly related to team performance.•Communication quality and frequency have different relationships with performance.•Additional types of communication exhibit different relationships with performance.•Team familiarity and virtuality moderate the relationship. Although it is consistently identified as a critical component of team performance, team communication is often conceptualized in a variety of manners. The present meta-analysis addresses this inconsistency by examining the moderating influence of communication characteristics, as well as other salient team and task characteristics, on the relationship between team communication and performance. The findings revealed several fundamental insights. First, communication quality had a significantly stronger relationship with team performance than communication frequency. Second, further distinguishing between different communication types, classifying communication into the eight most commonly measured communication forms (e.g., knowledge sharing, information elaboration), has further value; information elaboration has the strongest relationship with performance while self-report frequency and objective frequency have the weakest relationships. Third, familiar and face-to-face teams exhibited a stronger relationship between communication and performance. These results indicate the necessity of distinguishing between different communication types in both practical and theoretical applications of team science.